Diversity and distribution of chaetognaths of different marine environments along the Straits of Malacca - De Guzman, Heidi Jane (2011)
Two different study sites were selected along the coastal areas of the Straits of Malacca for the determination of the biodiversity and distribution of chaetognaths in polluted and pristine environments. These are the coastal waters off an industrial area, Kuala Juru (between 05°19.91 'N, 100023.75'E and 05°19.6B'N, 100022.95'E) and coastal waters off mangrove forest, Kuala Gula (between 04°55.19'N, 100027.B4'E and 04°55.01'N, 100027.76'E. Zooplankton and water samples from the coastal waters off Kuala Juru and coastal waters off Kuala Gula were collected monthly from August 2007 to July 200B. Samples for biodiversity study were collected by vertical tows (from the deepest depth at every station) from three randomly selected stations in each ecosystem using conical shaped (with mouth opening size of 0.30 m and 1.00 m length) plankton net with 100 urn mesh with an acrylic plastic cod end. Samples for biomass and taxonomic analyses were preserved in buffered formalin at 5% concentration. Chaeotognaths enumeration and identification were done under dissecting microscope. Biomass of the chaetognaths was determined using different standard techniques (wet, dry weight and ash free dry weight for total chaetognaths). A total of 11 species of chaetognaths from seven genera were identified from Kuala Gula samples, compared to nine species and four genera from Kuala Juru. The most abundant species in Kuala Gula was S. regularis (162.48 ind.rrrr'). Similarly, this species accounted the highest density in Kuala Juru (55.11 ind.rrn") .The mean Shannon Index (H') value for Kuala Gula and Kuala Juru were 2.3 and 2.1, respectively. The species richness (d) were d=2.6 for Kuala Gula and d=2.3 for Kuala Juru. Cluster analyses and multidimensional scaling analyses revealed two characteristics of chaetognath populations in the coastal areas. The coastal waters off a mangrove reserve was characterized by high-density and high species diversity, whereas the coastal waters off a polluted industrial area was characterized by a relatively low-density and low species diversity. Samples from three different ecosystems were analyzed for the determination of the distribution of chaetognaths from other coastal ecosystems along the Straits of Malacca. These three sampling locations were located in the coastal waters off a shrimp aquaculture farm (SAF), (between 03°15.11'N 101°17.79'E and 03°16.42'N 101°14.96'E); fish cage mariculture area (CMA); (between 03°00.67'N 101°16.27'E and 02°59.77'N 101°16.7'E), and seagrass area (SGA), (01°20.045'N 103°35.99'E and 01°19. 78'N 103°05.67'E). Cluster and multi-dimensional scale analysis revealed three characteristics of chaetognaths communities from the three coastal ecosystems. The mean Shannon Index (H') value for SAF overall was 1.9, 1.7 for CMA, and 1.6 for SGA, with d (Margalef's species richness) values of 2.0, 1.6, and 1.4 respectively. The coastal waters SAF was characterized by high-density values and high species diversity, CMA was characterized by a low-density values and low species diversity and similarly, the SGA was characterized by a low-density values and low species richness. In addition to different density and biodiversity between the polluted and unpolluted areas, individual chaetognath also showed some fouling on the body surface. Chaetognaths from the pristine environment showed the most fouling by organisms on the body surface compared to those from nonpolluted area. The highest percentage of biofouling invasion was aquatic fungus from the Kingdom Chromista (73.68%), followed by parasitic fungus (18.42%), and the least was bacteria (7.90%). Bacterial colonization (10.0%) was only observed in deformed chaetognaths collected from the polluted coastal waters off the industrial area. Although there was a high percentages of periphytic invasion on chaetognaths body collected from both sites, significantly higher (p<0.05) percentage of more destructive periphytes in the chaetognaths were found in Kuala Juru than in Kuala Gula. This study illustrated that chaetognaths distribution was influenced by geographical locations and the species characteristics of the environment. Aidanosagitta neglecta was found to be the most dominant chaetognath species which was able to tolerate variable environmental conditions. In addition, significantly (p<O.05) higher percentage of biofouling on chaetognath occurred in pristine environment.